1972
DOI: 10.21273/jashs.97.4.539
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability of Two Degenerative Sweet Corn Mutants II

Abstract: Two degenerative sweet corn mutants, C30, a mutant of P39, ‘Pee Wee’ a mutant of C30 and P39 were crossed with sweet corn inbred C15 to determine their relative abilities to promote heterosis in hybrids. Of the 3 inbreds, C30 had the greatest ability to promote heterosis when in combination with C l5; ‘Pee Wee’ was least effective. Evidently, not all degenerative mutants are capable of promoting marked heterotic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Variation was observed for ear weight, plant height, and ear height among the crosses, the highest yielding crosses involved C30. These results confirm previous results (Singleton, 1943; Lachman, 1972, 1974). Breeding experiments indicated that the differences in yield were due to a number of genetic factors (Singleton, 1948) Molecular data support this hypothesis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Variation was observed for ear weight, plant height, and ear height among the crosses, the highest yielding crosses involved C30. These results confirm previous results (Singleton, 1943; Lachman, 1972, 1974). Breeding experiments indicated that the differences in yield were due to a number of genetic factors (Singleton, 1948) Molecular data support this hypothesis.…”
Section: Discussionsupporting
confidence: 93%
“…In some cases, heterosis has been 1944, 1945Singleton and Nelson, 1945;Russell et al, observed in crosses between variants and the progenitor inbred. 1963;Lachman, 1971;Burr and Burr, 1981). Many of Causes of such variants and resulting heterosis are unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation